KNN and Webgis Classification to Recommend Mountain Location According to Hiker Abilities - Shagi Hisyam Al Fathony; Ani Dijah Rahajoe; Rifki Fahrial Zainal (JEECS (Journal of Electrical Engineering and Computer Sciences), 2022)
The increasing number of climbers has an impact on the need for a system that can recommend mountains for climbingaccording to the ability of climbers. This study aims to create a system that can help climbers determine the mountainaccording to their abilities. Researchers use one of the methods in data mining, namely classification, using the K =Nearest Neighbor (K-NN) algorithm.This research has produced a web-based system where this system can classify and provide recommendationsaccording to the ability of climbers. This system is equipped with a hiking trail map which is expected to help make iteasier for climbers to choose the mountain they will climb.